2020
DOI: 10.1016/j.celrep.2019.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Neurochemical Organization of the Drosophila Brain Visualized by Endogenously Tagged Neurotransmitter Receptors

Abstract: Highlights d Comprehensive T2A-GAL4 knockin resources for neurotransmitter receptors in flies d T2A-GAL4 can be converted into other reporters by RMCE d Quantitative analyses of receptor expression reveal segmentation of the fly brain d Four dopamine receptor proteins have distinct and dynamic subcellular localization

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
124
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(137 citation statements)
references
References 104 publications
13
124
0
Order By: Relevance
“…Among these, we focused on nAChRα1 , nAChRα2, nAChRα3, nAChRβ1 and nAChRβ2 because the knock-down of these genes in dsx + Tdc2 + ( tub >GAL80>, dsx-FLP; Tdc2-GAL4 ) or Tdc2 neurons ( Tdc2-GAL4 ) increased the GSC number in virgin females similar to ppk >ChAT RNAi ( Figure 6D and Figure 6—figure supplement 1A ). We then confirmed the expression of these acetylcholine receptor genes in Tdc2 neurons by generating a knock-in T2A-GAL4 line as previously described ( Kondo et al, 2020 ; Ihara et al, 2020 ) for each 5 nAChR subunit s and observed their expression with UAS-mCD8::GFP . All of the five knock-in-GAL4 expressions were detected in anti-Tdc2 positive neurons around the ovary, suggesting that the ovary-projecting dsx + Tdc2 + neurons expresses these nAChRs ( Figure 6—figure supplement 1B–F ).…”
Section: Resultsmentioning
confidence: 61%
See 2 more Smart Citations
“…Among these, we focused on nAChRα1 , nAChRα2, nAChRα3, nAChRβ1 and nAChRβ2 because the knock-down of these genes in dsx + Tdc2 + ( tub >GAL80>, dsx-FLP; Tdc2-GAL4 ) or Tdc2 neurons ( Tdc2-GAL4 ) increased the GSC number in virgin females similar to ppk >ChAT RNAi ( Figure 6D and Figure 6—figure supplement 1A ). We then confirmed the expression of these acetylcholine receptor genes in Tdc2 neurons by generating a knock-in T2A-GAL4 line as previously described ( Kondo et al, 2020 ; Ihara et al, 2020 ) for each 5 nAChR subunit s and observed their expression with UAS-mCD8::GFP . All of the five knock-in-GAL4 expressions were detected in anti-Tdc2 positive neurons around the ovary, suggesting that the ovary-projecting dsx + Tdc2 + neurons expresses these nAChRs ( Figure 6—figure supplement 1B–F ).…”
Section: Resultsmentioning
confidence: 61%
“…We also examined Oamb expression in the ovarian-somatic cells by two Oamb -knock-in GAL4 lines ( Deng et al, 2019 ; Kondo et al, 2020 ). However, we could not detect any reliable signals in the germarium or the mature follicle cells via these GAL4 lines with UAS-GFP and UAS-Stinger lines ( Figure 1—figure supplement 2A,B,C and D ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Neurotransmitter release from PPL1-γ2α′1 (MB296B) DANs in response to stimulation of the IP 3 R was investigated next. Presence of the mAChR was confirmed on to be present on Kenyon cells and mushroom body (Kondo et al, 2020). Though, requirement for the IP 3 R and the mAChR was restricted to 48-96 hrs APF, these data suggest that the neurotransmitter acetylcholine stimulates dopamine release in adult DANs through mAChR-IP 3 R signaling.…”
Section: The Ip 3 R Affects Neurotransmitter Release From Adult Dopammentioning
confidence: 77%
“…Drosophila melanogaster provides a powerful opportunity to map the fundamental architecture of neural circuits due to its complex yet tractable brain. With a nervous system of approximately 100,000 neurons and a rich genetic toolkit that offers the potential to selectively manipulate subsets of neurons in behaving animals, significant effort has been devoted to establishing a detailed map of neural connectivity in the fly (Aso et al, 2014a;Bates et al, 2020;Couto et al, 2005;Deng et al, 2019;Eichler et al, 2017;Eschbach et al, 2020;Fishilevich and Vosshall, 2005;Frechter et al, 2019;Grabe et al, 2015;Kondo et al, 2020;Li et al, 2020;Marin et al, 2020;Otto et al, 2020;Peng et al, 2011;Shao et al, 2014;Takemura et al, 2017;Zheng et al, 2018).…”
Section: Introductionmentioning
confidence: 99%